A stuck colonoscope in the chest cavity: An uncommon complication. Issue 8 (11th July 2020) - Shah, Muhammad Usman; Eissa, Ahmed; Caruso, Vincenzo; Bhusari, Sudhir
Abstract: Colonoscopy is generally considered a safe procedure, with a low rate of complications. Although rare, the migration of the colonoscope may represent life‐threatening events, requiring emergency treatment. We, herein, describe the case of an elective colonoscopy complicated by an irretrievable colonoscope that migrated, through a previous traumatic diaphragmatic hernia, in the chest cavity. This hernia was likely a chronic complication of a previous abdominal trauma. Several attempts to retrieve the scope were unsuccessful. After further investigations and collegial discussion, a left thoracotomy was performed, with the aim to retrieve the colonoscope and to reduce the hernia.